Przypadki Augie'ego Marcha - Bellow, Saul.; Bellow, Saul. (Warszawa : Panstwowy Instytut Wydawniczy, 1990)
Polish translation of a story of life in America in the period between the wars by the famous author, "The Adventures of Augie March."
Translation of: The adventures of Augie March.